Value management guidelines for the Malaysian construction industry - Jaapar, Aini; Takim, Rohana; Ahmad Bari, Nor Azmi; Endut, Intan Rohani (Faculty of Design & Architecture, Universiti Putra Malaysia, 2008)
As a result of a rigorous concatenated exploratory research using mixed methodologies, sustainable Value Management (VM) Guidelines for the Malaysian construction industry were developed. It is hoped to assist the future driving force in the further development of VM in Malaysia as well as paving the way for better implementation of VM which promises improved value for the clients of the Malaysian construction industry. Since there is no sound academic base and lack of understanding by the construction clients and the professional consultants towards VM in Malaysia, this paper is to enlighten the Malaysian construction industry on the availability and the existence of the prototype VM Guidelines resulting from the undertaken research